The SPARC initiative: a catalyst for change - Savenije, Bas (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2004)
SPARC was started in 1997 by a number of large research libraries in the US. Its main goal was to restore a competitive balance of the STM journals publishing market. A number of programmatic areas were initiated in order to realize this goal: SPARC Alternatives, SPARC Leading Edge, SPARC Scientific Communities, and SPARC Communication and Advocacy. Since two years SPARC puts a special emphasis on Open Access, including institutional repositories. The paper gives an overview of the activities of SPARC and its partners in these areas. The results are evaluated and compared with the measures defined in 1997. Finally, the paper describes the possibilities for libraries to contribute to the realization of SPARC's goals.